Gonadotroph tumours with a low SF‐1 labelling index are more likely to recur and are associated with enrichment of the PI3K‐AKT pathway. (20th December 2020) - Hickman, Richard A.; Bruce, Jeffrey N.; Otten, Marc; Khandji, Alexander G.; Flowers, Xena E.; Siegelin, Markus; Lopes, Beatriz; Faust, Phyllis L.; Freda, Pamela U.
Abstract: Aims: The gonadotroph tumour (GT) is the most frequently resected pituitary neuroendocrine tumour. Although many symptomatic GT are successfully resected, some recur. We sought to identify histological biomarkers that may predict recurrence and explore biological mechanisms that explain this difference in behaviour. Methods: SF‐1 immunohistochemistry of 51 GT, a subset belonging to a longitudinal prospective cohort study (n = 25), was reviewed. Four groups were defined: Group 1—recently diagnosed GT (n = 20), Group 2—non‐recurrent GT with long‐term follow up (n = 11), Group 3—initial resections of GT that recur (n = 7) and Group 4—recurrent GT (n = 13). The percentage of SF‐1 immunolabelling in the lowest staining fields (SF‐1 labelling index (SLI)) was assessed and RNA sequencing was performed on 5 GT with SLI <80% and 5 GT with SLI >80%. Results: Diffuse, strong SF‐1 immunolabelling was the most frequent pattern in Groups 1/2, whereas patchy SF‐1 staining predominated in Groups 3/4. There was a lower median SLI in Groups 3/4 than 1/2. Overall, GT with SLI <80% recurred earlier than GT with SLI >80%. Differential expression analysis identified 89 statistically significant differentially expressed genes (FDR <0.05) including over‐expression of pituitary stem cell genes ( SOX2, GFRA3 ) and various oncogenes (e.g. BCL2, ERRB4) in patchy SF‐1 GT. Gene set enrichment analysis identified significant enrichment of genes involved in the PI3K‐AKT pathway. Conclusions: We speculate that patchy SF‐1 labelling in GT reflects intratumoural heterogeneity and are less differentiated tumours than diffusely staining GT. SF‐1 immunolabelling patterns may have prognostic significance in GT, but confirmatory studies are needed for further validation. Abstract : Gonadotroph tumours (GT) with a low SF‐1 labelling index (SLI) are more prone to recur and have a different transcriptome than those with a high SLI. GT with patchy SF‐1 immunolabelling may reflect intratumoral heterogeneity and less differentiation than those with diffuse staining.